Wireless Water Level Informer Using IOT - D. Mansoor Hussain Aakhil Karthikkeyan V Hariharan R Bharath Kumar J (International Journal of Advanced Science and Technology, 2020)
The Earth’s surface is mostly covered with water but only very less percentage of it is useful. So, the major issue here is to conserve the water level present on the earth. Hence measuring the water level is a big task in front of us. In this paper the Ultrasonic Sensors will help measure the water levels. In this paper we will introduce the ECHO for distance measurement. The sonar waves are used for echolocation, which helps in the measurement of distance. When sound waves strike an obstacle in its path they return to the origin as ECHO. Hence the time calculation is easy because one has to calculate only its traveling time sound which is the sound that travels from the source and the time it takes to return to the origin after hitting an obstacle.. The sensor is automatically programmed to keep informed if the water level goes very low